Fiscal Decentralization and Income Inequality: A Prediction Using the SEM Model - Juliansyah Roy; Adi Wijaya; Dio Caisar Darma; Erwin Kurniawan A (Universitas Hayam Wuruk Perbanas, 2021)
Economic development in a region is not only measured by the fiscal dimension andthe economic growth but also based on the income distribution. This study aims toanalyze the effect of fiscal decentralization on investment, economic growth, economic structure, employment opportunities, and income inequality between districts/cities in East Kalimantan Province, Indonesia. This study uses panel data (2013-2019) of the amalgamation of seven districts and three cities in East Kalimantan Province, analyzed using the Structural Equation Model (SEM). The findings show that regional tax plays a crucial role in enhancing regional investment, economic growth, and employment opportunities. It is also important for reducing the economic structure imbalance and income inequality. Profit-sharing funds improve regional investment, economic growth, and employment opportunities. At the same time, special allocation increases employment opportunities and economic structure imbalance. Furthermore, regional retribution increases employment opportunities and reduces the economic structure imbalance, but it harms regional economic growth. The practical implications offer solutions to the realization of local revenue sources for economic development and alleviation of social problems, such as employment opportunities and inequality in welfare.